Green synthesis of multifunctional carbon dots from coriander leaves and their potential application as antioxidants, sensors and bioimaging agents1. Issue 12 (21st June 2015) - Sachdev, Abhay; Gopinath, P.
<x xml:space="preserve">Abstract</x> A facile one-step hydrothermal synthesis of multifunctional carbon dots from coriander leaves for versatile applications is reported.